Glossary - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
E-mail: Text messages sent over the internet from one individual to one or many individuals. Such text messages can be sent to any e-mail address worldwide for the same cost as sending it to an address next door.E-mail conference: Opinions/queries...